DIVERSITY OF GROUND-ACTIVE SPIDER COMMUNITY ACROSS DIFFERENT TROPICAL FOREST HABITATS AND CLIMATE CONDITIONS IN NORTHERN VIETNAM - Thi Ha, Do; Thi Thu Ha, Dinh; Dinh Sac, Pham (HNUE Journal of Science: Journal of Natural Sciences, 2025)
A year-long survey of ground-active spiders was conducted in three typical tropical forest areas of Northern Vietnam, each characterized by distinct climatic conditions: Cuc Phuong National Park (CPNP, tropical monsoon climate of the Red River Delta), Tam Dao National Park (TDNP, high-elevation tropical monsoon climate), and Cat Ba National Park (CBNP, maritime climate). Four types of habitats were selected in each region: natural forest and disturbed forest (both with multi-layered vegetation structures), and shrubland and acacia plantation (both with simple-layer vegetation structures). Spiders were sampled using pitfall traps. Cursorial hunters and ground-level web builders were the dominant guilds in all study areas. Spider diversity was compared across the study areas. Cluster analysis showed that the species composition in the maritime climate area (CBNP) was significantly different from that in the other areas. Spider diversity was also compared between habitats with multi-layer vegetation structures (multi-LVS) and those with simple-layer vegetation structures (simple-LVS). Both species composition and spider abundance were higher in habitats with multi-LVS than those with simple-LVS. The results of this study highlight the importance of preserving natural ecological processes to conserve biodiversity in multi-VLS habitats and to aid in the restoration of biodiversity in simple-LVS habitats. Keywords: ground-active spiders, regional climate, Northern Vietnam.